What Really Builds Competitive Advantage in Creative Culinary MSMEs? The Dominance of Operational Capabilities - Yuaniko Paramitra; Fatimah Fatimah; Fajar Cahyo Utomo (SAN Scientific, 2026)
This study analyzes the influence of entrepreneurial marketing and operational capabilities on competitive advantage among coffee shop MSMEs in Bekasi City. Increasing competition in the culinary industry, particularly the food and beverage sector, encourages MSMEs to develop effective strategies to sustain competitiveness. The research employed a quantitative approach using questionnaire data collected from coffee shop MSME owners in Bekasi City. Data analysis included multiple linear regression, t-tests, F-tests, and correlation analysis. The results indicate that entrepreneurial marketing and operational capabilities positively and significantly affect competitive advantage. However, operational capability demonstrates a stronger influence than entrepreneurial marketing. This finding suggests that competitive advantage in the coffee shop industry depends not only on marketing creativity but also on operational consistency, service quality, efficiency, and the ability to meet customer expectations. Consumers place greater value on product quality and service experience, making operational excellence a critical factor for long-term competitiveness. The study highlights a shift in MSME competitive strategies from marketing orientation toward stronger operational capability development. Therefore, coffee shop MSMEs should strengthen internal operational systems, employee competence, and service efficiency while continuing innovative marketing efforts to achieve sustainable competitive advantage.